O‘ZBEK ADABIYOTIDA ESSE JANRI ISTIQBOLI - Azilova, Z.G. (SCIENCE and SOCIETY, 2021)
The article describes the formation, development, prospects of the essay genre in Uzbek literature, as well as the genres of essays and badia. This article provides information about essays in Uzbek literature. The statements of writers about the genres of essays, memoirs, badia are comparatively analyzed.